Optoacoustic imaging of the brain in a cachexia-inducing pancreatic cancer xenograft - Yousf, Saleem; Penet, Marie-France; Brannen, Andrew; Winnard, Paul; Mironchik, Yelena; Krishnamachary, Balaji; Bhujwalla, Zaver M. (Frontiers in Oncology, 2025)
Pancreatic cancer-induced cachexia drives co-morbidities that result in a poor quality of life. To expand understanding of the effects of cachexia on the brain here, for the first time, we used noninvasive oxygen enhanced (OE) multispectral optoacoustic tomography (MSOT) to evaluate the ability of the brain vasculature to respond to oxygen breathing in an established xenograft model of pancreatic cancer-induced cachexia. Studies were performed with mice bearing cachexia inducing Pa04C tumors, non-cachexia inducing Panc1 tumors and non-tumor bearing mice. OE-MSOT identified a reduced oxygen carrying capacity in the brain vasculature of mice with cachexia inducing Pa04C tumors, compared to non-tumor bearing mice, and mice with non-cachexia inducing Panc1 tumors. Brain volumes, quantified in mice with MSOT, were significantly reduced in Pa04C tumor-bearing mice compared to non-tumor bearing mice. Our data have identified the inability of brain vasculature to increase oxygenation in response to oxygen breathing in cachectic mice as a new mechanism that may contribute to cachexia-induced morbidity.